A pilot trial of complement inhibition using eculizumab to overcome platelet transfusion refractoriness in human leukocyte antigen allo‐immunized patients. (21st February 2020) - Vo, Phuong; Purev, Enkhtsetseg; West, Kamille A.; McDuffee, Emily; Worthy, Tatyana; Cook, Lisa; Hawks, Geri; Wells, Brian; Shalabi, Reem; Flegel, Willy A.; Adams, Sharon D.; Reger, Robert; et al.
Summary: Heavily transfused patients frequently develop human leukocyte antigen (HLA) allo‐immunization resulting in platelet transfusion refractoriness and a high risk for life‐threatening thrombocytopenia. Data suggest complement activation leading to the destruction of platelets bound by HLA allo‐antibodies may play a pathophysiologic role in platelet refractoriness. Here we conducted a pilot trial to investigate the use of eculizumab, a monoclonal antibody that binds and inhibits C5 complement, to treat platelet transfusion refractoriness in allo‐immunized patients with severe thrombocytopenia. A single eculizumab infusion was administered to 10 eligible patients, with four (40%) patients overcoming platelet refractories assessed measuring the corrected platelet count increment (CCI) 10–60 min and 18–24 h post transfusion. Responding patients had a reduction in the requirement for subsequent platelet transfusions and had higher post‐transfusion platelet increments for 14 days following eculizumab administration. Remarkably, three of the four responders met CCI criteria for response despite receiving HLA‐incompatible platelets. Our results suggest that eculizumab has the ability to overcome platelet transfusion refractoriness in patients with broad HLA allo‐immunization. This study establishes proof of principle that complement inhibition can treat platelet transfusion refractoriness, laying the foundation for a large multicentre trial to assess the overall efficacy of this approach (ClinicalTrials.gov, identifier: NCT02298933).